(untitled) (REMUNOM, 2024)
Breast cancer is one of the most common neoplastic presentations among women, primarily affecting those from higher social classes but showing higher mortality rates among patients from lower socioeconomic strata. Among its various forms, triple-negative breast cancer (TNBC) is known for having the worst prognosis and highest recurrence rate. This scoping review aimed to highlight factors contributing to the differential diagnosis of TNBC using the molecular technique of polymerase chain reaction (PCR). A search was conducted in databases such as PubMed, Embase, Scopus, Web of Science, and Cochrane Library, guided by the question: "What is the role of PCR in the early molecular diagnosis of TNBC?" Eight studies were included, identifying the presence of genes such as VEGFA, SRC, PARP1, PTK2, RAF1, FGR3, KRAS, AZGP1, KRT19, and PIGR as key to distinguishing this subtype of cancer. PCR is a rapid and minimally invasive technique that contributes to the diagnosis and monitoring of TNBC. Future research should focus on establishing specific thresholds to standardize the test, particularly emphasizing genes like VEGFA, KRAS, AZGP1, KRT19, and PIGR.